2011
DOI: 10.1152/ajpregu.00624.2010
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors responsible for switching on the SO42−excretory system in the kidney of seawater eels

Abstract: 2Ϫ regulation between FW and SW. We previously showed that the expression of renal SO 4 2Ϫ transporter genes, FW-specific Slc13a1 and SW-specific Slc26a6a, changes profoundly after transfer of FW eels to SW, which results in the decrease in plasma SO 4 2Ϫ concentration after 3 days in SW. In this study, we attempted to identify the environmental factor(s) that trigger the switching of SO 4 2Ϫ regulation using changes in plasma and urine SO 4 2Ϫ concentrations and expression of the transporter genes as markers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…In fact, the total negative charge of Cl -and SO 4 2-was almost the same in three euryhaline fishes in freshwater and seawater in the present study (data not shown), and plasma Cl -was inversely correlated with plasma SO 4 2-concentration (Watanabe and Takei, 2011b). Thus, freshwater eels appear to have an unusually high tolerance to hypersulfatemia or a unique mechanism to neutralize the toxic effects of excess SO 4 2-.…”
Section: High Plasma So 4 2-concentrations In Freshwater Eelssupporting
confidence: 52%
See 2 more Smart Citations
“…In fact, the total negative charge of Cl -and SO 4 2-was almost the same in three euryhaline fishes in freshwater and seawater in the present study (data not shown), and plasma Cl -was inversely correlated with plasma SO 4 2-concentration (Watanabe and Takei, 2011b). Thus, freshwater eels appear to have an unusually high tolerance to hypersulfatemia or a unique mechanism to neutralize the toxic effects of excess SO 4 2-.…”
Section: High Plasma So 4 2-concentrations In Freshwater Eelssupporting
confidence: 52%
“…Concerning the transcellular pathway, little is known about SO 4 2-transporters and channels in the gills. In the intestine, solute carrier (Slc) 26a6 family members, anion exchangers that potentially transport SO 4 2-, have been identified in the eel (Watanabe and Takei, 2011b) and pufferfish (Kurita et al, 2008). However, Slc26a6 localized on the apical membrane of epithelia may secrete SO 4 2-into the lumen in exchange for Cl -, as has been shown in the proximal tubule of seawater eel kidney (Watanabe and Takei, 2011a).…”
Section: So 4 2-influx From the Environmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Then, the SO 4 2− is moved across the basolateral membrane by an SO 4 2− /2HCO 3 − -exchanger (SLC26a1), which is energized by an SO 4 2− gradient across the basolateral membrane [ 316 ]. In Japanese eels, SO 4 2− may play a role in osmoregulation in freshwater because serum SO 4 2− is elevated in freshwater (~19 mM vs ~1 mM in saltwater), whereas Cl − is reduced compared with the Japanese eels in saltwater or other fish in freshwater [ 316 , 318 ].…”
Section: Transporters and Physiology Of Individual Ionsmentioning
confidence: 99%
“…Therefore, the SW fish kidney is a good model of renal secretion of divalent ions. Recently, Cl Ϫ /SO 4 2Ϫ exchangers Slc26a6A and Slc26a6B were identified as mediating renal SO 4 2Ϫ secretion in seawater (22,(52)(53). However, ion transporters that are involved in renal Mg 2ϩ or Ca 2ϩ secretion have not yet been identified.…”
mentioning
confidence: 99%